Experimental investigation of Rijke-type pulse combustor for drying application - Tan, Eugene Jui Chuan. (2013)
In today world, foods are being transport across the global by air, land or sea. However, foods which have high moisture content are perishable meaning it could not be storage long or are need to be storage in a freezer before transporting. Drying food cheaply and effectively is thus important in order to transport perishable food over great distance. The pulse combustor is the answer to the problem. By making use of vibration and hot air, it allow product to be dry in a short time, lowing operation and maintenance cost. To better improve the drying process, a better understanding of the combustion instability is needed. The objective of this project is to understand and find way to better improve the efficiency of drying using the pulse combustor.